Asia-Pacific Regional Outlook. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Looking ahead, prospects are relatively bright. Regional growth is expected to amount to 6 percent both this year and next, propelled by vigorous exports and strong domestic demand in China and India. Meanwhile, headline inflation is expected to remain around 3-3 1\2 percent, as lower food prices offset the impact of higher oil prices. At the same time, the region's current account balance is forecast to remain around 3 percent of GDP, albeit with large changes in its distribution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet